2021
DOI: 10.1371/journal.pone.0260510
|View full text |Cite|
|
Sign up to set email alerts
|

Individual dairy cow identification based on lightweight convolutional neural network

Abstract: In actual farms, individual livestock identification technology relies on large models with slow recognition speeds, which seriously restricts its practical application. In this study, we use deep learning to recognize the features of individual cows. Alexnet is used as a skeleton network for a lightweight convolutional neural network that can recognise individual cows in images with complex backgrounds. The model is improved for multiple multiscale convolutions of Alexnet using the short-circuit connected Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The literature [ 28 ] uses ReXNet 3D for cow behavior recognition and its model size is 14.3 MB with low accuracy, which is 10.69 MB larger than our model, in addition, its FLOPs are 15.8 G, which is also much larger than our model. Finally, compared with our previous work [ 29 ], The model in this study has a good performance improvement in both recognition accuracy and model lightweight, overcoming the deficiencies in recognition accuracy caused by complex backgrounds and speckle distortion from the spatial dimension, improving 0.63 percentage points compared to previous work, and also reducing the model size by 4.97 MB using the linear operation of ghost, making the model more lightweight.…”
Section: Resultsmentioning
confidence: 71%
“…The literature [ 28 ] uses ReXNet 3D for cow behavior recognition and its model size is 14.3 MB with low accuracy, which is 10.69 MB larger than our model, in addition, its FLOPs are 15.8 G, which is also much larger than our model. Finally, compared with our previous work [ 29 ], The model in this study has a good performance improvement in both recognition accuracy and model lightweight, overcoming the deficiencies in recognition accuracy caused by complex backgrounds and speckle distortion from the spatial dimension, improving 0.63 percentage points compared to previous work, and also reducing the model size by 4.97 MB using the linear operation of ghost, making the model more lightweight.…”
Section: Resultsmentioning
confidence: 71%
“…Figure 4b shows the NAM spatial attention submodule, which is calculated as shown in Equation (5). The scaling factor of BN is applied to the spatial dimension to measure the importance of a pixel, which is called pixel normalization.…”
Section: Feature Extraction Backbone Network With a Normalized Attent...mentioning
confidence: 99%
“…However, the traditional methods rely on manually selecting features, and the results of feature extraction directly affect the performance of individual cow recognition. With the development of deep learning and computer vision technology, convolutional neural networks (CNNs) have shown strong feature extraction abilities, and they have been applied to the field of livestock by many researchers [4][5][6][7][8]. Hu et al [9] proposed a novel non-contact cow identification method based on the fusion of deep parts of features by making good use of the YOLO (You Only Look Once) method to detect the cows' heads, trunks, and legs; they built three CNN models to recognize the identities of cows together, and they achieved an accuracy of 98%.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1,020 original images from 102 cows were collected and some examples were shown in Figure 1. It was observed that the dataset scale has a huge impact on the performance of the training network such that when the feature dimensions of the space sample are greater than the training sample's number, the model tends to overfit [19]. Therefore, the training and , 80:20 [21], and 67:33 [22], using python script algorithm in order to determine the optimal model accuracy.…”
Section: Data Acquisitionmentioning
confidence: 99%